A high-strength concrete internal curing agent and its preparation method and application
By using composite nonionic surfactants and highly absorbent composite materials, combined with microcrystalline mica and seaweed fiber powder, a high-strength concrete internal curing agent was prepared, which solved the shortcomings of traditional internal curing agents in terms of mechanical properties and durability, and achieved the goal of achieving The volume stability and mechanical properties of concrete are improved.
Patent Information
- Application Number
- CN202211412444.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-11-11
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete admixtures, and specifically relates to a high-strength concrete internal curing agent and a preparation method and application thereof. Background Art
[0002] The increase in concrete strength can effectively reduce the deadweight of buildings. This advancement in concrete technology has led to the increasingly widespread use of high-strength and high-performance concrete in various building structures since the 1980s, especially in the construction of high-rise buildings and long-span bridges. In high-strength and high-performance concrete, the water-cement ratio is usually very low and the amount of cement is large, so the internal pore size of the concrete is small and the alkalinity of the pore solution is high, which can show good mechanical properties and durability; however, the low water-cement ratio will also cause problems such as reduced relative humidity inside the concrete and increased material shrinkage. In addition, the lack of moisture inside the concrete will also lead to limited late strength development of high-strength concrete and early cracking, thus affecting mechanical properties and durability.
[0003] At present, the internal curing technology of concrete is a curing method that can effectively avoid shrinkage and cracking of concrete during the curing process. The widely used internal curing materials mainly include porous lightweight aggregate (LWA), super absorbent resin (SAP), and shrinkage reducing agent (SRA). During use, they will have some disadvantages that affect the performance of concrete to a certain extent, such as: 1) The addition of LWA will affect the mechanical properties of concrete to a certain extent. How to maintain the other properties of concrete in good condition while maintaining the internal curing effect still needs further research; 2) For the internal curing system based on SAP, different preparation processes and raw materials will affect the water absorption rate, particle size, water release rate and other physical properties of SAP. In addition, for SAP applied in actual projects, how to control its properties during transportation and pouring is also a problem currently faced; 3) For the internal curing system based on SRA, although the shrinkage reducer can reduce the autogenous shrinkage cracking of concrete, due to its compatibility with other admixtures and other problems, it usually affects the mechanical properties or other performance of concrete, such as reducing the plasticizing effect of high-efficiency water reducer, reducing the shrinkage effect of shrinkage reducer, and significantly reducing the mechanical properties of cement-based materials (causing the strength of concrete to drop by more than 10-15%).
[0004] Therefore, further exploring new simple and efficient high-strength concrete internal curing agents and optimizing their preparation processes are of great research and application significance. Summary of the invention
[0005] The main purpose of the present invention is to provide a new type of internal curing material in view of the problems and shortcomings of the prior art, which has excellent water retention and water release properties, can simultaneously improve the volume stability, mechanical properties and durability of concrete, and has wide applicability; and the preparation method involved is relatively simple, the reaction conditions are mild, and the preparation cycle is short, which is suitable for promotion and application.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a high-strength concrete internal curing agent comprises the following steps:
[0008] 1) dissolving a composite nonionic surfactant in water, adding a sodium silicate solution and methyldimethoxysilane thereto, and stirring; then adding ammonia water under stirring conditions, mixing uniformly, to obtain a polymer A; wherein the composite nonionic surfactant is composed of fatty alcohol polyoxyethylene ether and isomeric tridecanol polyoxyethylene ether;
[0009] 2) mixing microcrystalline muscovite ultrafine powder, seaweed fiber powder, N,N-methylenebisacrylamide (crosslinking agent) and water uniformly, preliminarily stirring the obtained mixture at room temperature, then adding acrylic acid and heating and stirring uniformly, performing glow discharge electrolytic plasma treatment, then heating and stirring reaction, and cooling to room temperature to obtain polymer B;
[0010] 3) Mixing polymer A and polymer B, stirring, neutralizing to a neutralization degree of more than 90%, and then washing and drying to obtain the internal curing agent.
[0011] In the above scheme, the microcrystalline muscovite ultrafine powder has a particle size D 90 ≤3μm, loose density ≤0.20g / cm 3 ; Sand content ≤0.2%, SiO2 content is 45~48%, Al2O3 content is 25~30%.
[0012] In the above solution, the average particle size of the seaweed fiber powder is 30-40 μm.
[0013] In the above scheme, the mass ratio of fatty alcohol polyoxyethylene ether to isomeric tridecanol polyoxyethylene ether in the composite nonionic surfactant is 1:(1-1.5).
[0014] In the above scheme, the raw materials used in step 1) and their weight proportions include: 4800-5200 parts of water, 0.5-1 part of composite nonionic surfactant, 20-25 parts of sodium silicate solution, 75-80 parts of methyldimethoxysilane, and 0.5-1 part of ammonia water.
[0015] In the above scheme, the pH value of the sodium silicate solution is 11-13, and the mass concentration is 30-40%.
[0016] Furthermore, the mass concentration of the ammonia water is 25-28%.
[0017] In the above scheme, the stirring treatment step in step 1) takes 40 to 50 minutes; the mixing time after adding ammonia water is 10 to 15 minutes.
[0018] In the above scheme, the raw materials used in step 2) and their weight proportions include: 45-50 parts of microcrystalline muscovite ultrafine powder, 10-15 parts of seaweed fiber powder, 8-10 parts of N,N-methylenebisacrylamide, 8250-9000 parts of water, and 900-1100 parts of acrylic acid.
[0019] In the above scheme, the time of the initial stirring in 2) is 40 to 50 minutes.
[0020] In the above scheme, the temperature used in the heating and stirring uniform step in step 2) is 50-55°C and the time is 15-20 minutes; the temperature used in the heating and stirring reaction step is 55-60°C and the time is 15-20 minutes.
[0021] In the above scheme, the glow discharge electrolytic plasma treatment step includes: inserting two electrodes and discharging for 2 to 3 minutes under voltage conditions of 180 to 220V, 480 to 520V, and 780 to 820V respectively.
[0022] Furthermore, during the glow discharge electrolytic plasma treatment process, adjacent voltage gradients increase by 280 to 320V.
[0023] In the above scheme, the mixing and stirring time in step 3) is 100 to 120 minutes.
[0024] In the above scheme, the washing step in step 3) includes: washing with water and washing with ethanol in sequence; the drying step includes: sealing and placing in an oven at 50-55°C for 22-24 hours, and placing in a dryer for drying for 4-6 hours after removing the seal.
[0025] The high-strength concrete internal curing agent prepared according to the above scheme has a tap water absorption rate of 380-400g / g, and a water retention rate of more than 90% after immersion for 24 hours; it has excellent water retention and water release properties, and adding an appropriate amount of high-strength concrete internal curing agent can improve the volume stability, mechanical and durability of concrete. In terms of volume stability, the shrinkage rate of concrete at the age of 28 days can be reduced by 18-20%, and in terms of mechanical properties, the compressive strength of cement-fly ash-mineral powder ternary cementitious material system concrete at the age of 28 days under standard curing can be increased by 8-10%, and in terms of durability, the 56-day electrical flux of concrete under standard curing can be reduced by 150-200C, and the carbonization depth can be reduced by 25-30%.
[0026] The internal curing agent obtained by the invention is used for preparing high-strength concrete, and its dosage in the high-strength concrete is 1.8-2.2% of the mass of the cementitious material.
[0027] The components and their weights include:
[0028] Formula 1, C60 grade: cement 395~405kg / m 3 , fly ash 45~55kg / m 3 , mineral powder 105~115kg / m 3 , sand 600~610kg / m 3 , stone 1060~1080kg / m 3 , water 140~150g / m 3 , polycarboxylate water reducer 12.5~13.5kg / m 3 , high strength concrete internal curing agent 10.5~12.5kg / m 3 ;
[0029] Formula 2, C70 grade: cement 495~505kg / m 3 , fly ash 45~55kg / m 3 , mineral powder 45~55kg / m 3 , sand 915~930kg / m 3 , stone 770~780kg / m 3 , water 140~150g / m 3 , polycarboxylate water reducer 14.5~15.5kg / m 3 , high strength concrete internal curing agent 10.5~13.0kg / m 3 .
[0030] The principle of the present invention is:
[0031] The present invention firstly uses sodium silicate and methyl dimethoxysilane as main raw materials, composite fatty alcohol polyoxyethylene ether and isomeric tridecanol polyoxyethylene ether as composite nonionic surfactants, and introduces a siliceous porous water-retaining material (polymer A) through reaction, so that the unreacted water inside the concrete can be fully present in the capillary pores, thereby avoiding the generation of capillary pressure, thereby reducing the shrinkage cracking of the concrete, and at the same time, increasing the amount of hydration products in the concrete, reducing the porosity of the concrete, and refining the pore structure; on the other hand, the introduction of ultrafine muscovite powder and seaweed fiber powder can fill the microscopic pore structure of the concrete material from the perspective of physical properties while ensuring the water absorption and water retention functions of the internal curing material, and combining The fiber toughening effect of seaweed fiber powder improves the volume stability, mechanical and durability of concrete materials. In addition, the glow photoelectrolysis method is used to initiate the preparation of highly water-absorbent composite materials (polymer B), and combined with gradient discharge conditions, it effectively improves problems such as instability of the polymerization process (violent polymerization, etc.) and simultaneously improves the reaction efficiency. Finally, the above two types of polymers are used in combination to overcome the problem that traditional internal curing materials are prone to adversely affect the performance of concrete, and further enhance the water absorption and water retention properties of a single type of polymer. The advantages are complementary and the adaptability is excellent. The internal curing material's own performance and its comprehensive application effect in concrete can be comprehensively improved from both physical and chemical levels.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1) The high-strength concrete internal curing agent obtained by the present invention has good water retention and water release properties, and has good dispersibility, and can provide uniform curing for the internal structure of concrete; it can effectively improve the volume stability of the obtained concrete, reduce the shrinkage rate, and simultaneously improve its compressive and flexural strength; and overall improve the mechanical properties and durability of the concrete;
[0034] 2) The overall preparation process of the present invention has mild conditions, controllable reactions, no secondary pollution, and can significantly improve the comprehensive improvement effect of the obtained internal curing agent, which has important research and application significance. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] In the following examples, the cement used is Qingsong PO 42.5R cement; the fly ash is F·III fly ash from Honger Power Plant, with a fineness of 35%; the mineral powder is Baoxin Shengyuan S75 mineral powder, with a specific surface area of 395m 2 / kg; the sand is the source sand of concrete, with a fineness modulus of 3.4, a moisture content of 2.5%, and a mud content of 1.1%; the stone is the source stone of concrete with a particle size of 5-20mm, a mud content of 0.4%, a crushing index of 3%, and an apparent density of 2670kg / m 3 The water reducer is a polycarboxylic acid high-performance water reducer produced by Kehuida Chemical Building Materials Co., Ltd., with a solid content of 12.15% and a water reduction rate of 27%;
[0037] In the following examples, the prepared internal curing agent is in the form of white powder with an average particle size of 20 to 30 μm, and its dosage in concrete is 2% of the mass of the cementitious material.
[0038] In the following embodiments, the glow discharge electrolytic plasma treatment uses a DC voltage-stabilized power supply device, which can perform voltage transformation and control to achieve voltage transformation and regulation within the range of 0-1500V.
[0039] Example 1
[0040] A high-strength concrete internal curing agent, the preparation method of which comprises the following steps:
[0041] 1) Add 5000 parts (by weight, the same below) of water into a beaker, weigh 0.5 parts of a composite nonionic surfactant according to a composite ratio of fatty alcohol polyoxyethylene ether and isomeric tridecanol polyoxyethylene ether of 1:1, add it to the water, place it in a 50°C water bath and stir to dissolve; then add 20 parts of sodium silicate solution (mass concentration of 35%) and 80 parts of methyldimethoxysilane, stir well for 40 minutes, then slowly add 0.5 parts of ammonia water (mass concentration of 25%), stir rapidly (stirring rate of 300r / min) for 10 to 15 minutes while adding, and then seal it, which is recorded as polymer A;
[0042] 2) At the same time as step 1), add ultrafine microcrystalline muscovite powder (particle size D 90 =3μm, loose density = 0.20g / cm 3 ) 45 parts, seaweed fiber powder (fiber strength: 1.8d, average particle size of 30μm) 15 parts, N,N-methylenebisacrylamide (chemically pure) 9 parts and water 8500 parts, the mixture was initially stirred at room temperature for 40 minutes, then 1000 parts of acrylic acid (analytical pure) was added and the temperature was raised to 50°C, and the stirring was continued for 15 minutes. Two electrodes were inserted and gradient discharge was performed at 200V, 500V, and 800V for 2 minutes respectively, and then the temperature was raised to 60°C and the reaction was continued to be fully stirred for 15 minutes, and then cooled to room temperature, which was recorded as polymer B;
[0043] 3) The obtained polymer A and polymer B are mixed and stirred for 100 minutes, neutralized with NaOH (30%) to a neutralization degree of 90%, then washed with water several times, washed with ethanol, sealed and placed in a 50° C. oven for 24 hours, and after removing the seal, placed in a dryer and dried for 5 hours to obtain the high-strength concrete internal curing agent.
[0044] According to the test, the tap water absorption rate of the internal nourishing agent obtained in this embodiment is 390g / g, and the water retention rate after soaking for 24 hours is 92.2%.
[0045] Application Example 1
[0046] The high-strength concrete internal curing agent obtained in Example 1 is applied to prepare high-strength concrete (C60 grade), and the specific steps include:
[0047] The obtained internal curing agent is fully stirred in water, and then coarse and fine aggregates and cementitious materials (total design dosage is 560kg / m 3 ) was dry-mixed in a mixer for 40 seconds, and finally the internal curing mixture was poured into the mixer and fully mixed for 3 minutes. The slump of the concrete was controlled at (200±20) mm by adjusting the amount of water reducing agent. The specific mix ratio is shown in Table 1, and the performance test results of the obtained concrete are shown in Table 2.
[0048] Table 1 Concrete mix ratio (kg / m 3 )
[0049] Group cement Fly ash Mineral powder sand stone water Water reducing agent Internal curing agent Benchmarks 400 50 110 605 1070 144 13.2 Application Example 1 400 50 110 605 1070 144 13.2 11.0
[0050] Table 2 Performance test results of high-strength concrete obtained in Application Example 1
[0051] Group Shrinkage expansion ratio (%) Compressive strength(MPa) Electric flux (C) Carbonization depth (mm) Age 28d 28d 56d 56d Benchmarks -0.055 73.8 720 3.26 Application Example 1 -0.045 79.7 540 2.45
[0052] The above results show that the high-strength concrete obtained in this application example can simultaneously improve the volume stability, mechanical properties and durability compared with the benchmark group without internal curing agent, as follows: in terms of volume stability, the shrinkage rate of concrete at the age of 28 days is reduced by 18%; in terms of mechanical properties, the compressive strength of concrete at the age of 28 days under standard curing is increased by 8%; in terms of durability, for concrete under standard curing, the 56d electric flux is reduced by 180C and the carbonization depth is reduced by 25%.
[0053] Example 2
[0054] A high-strength concrete internal curing agent, the preparation method of which comprises the following steps:
[0055] 1) Add 5000 parts of distilled water into a beaker, weigh 0.5 parts of a composite nonionic surfactant according to the composite ratio of fatty alcohol polyoxyethylene ether and isomeric tridecanol polyoxyethylene ether of 1:1.5, add it to the water, place it in a 50°C water bath and stir to dissolve; then add 25 parts of sodium silicate solution (mass concentration of 35%) and 75 parts of methyldimethoxysilane, stir well for 40 minutes, then slowly add 0.5 parts of ammonia water (mass concentration of 25%), stir rapidly while adding (stirring rate of 300r / min for 10 to 15 minutes), and then seal it, which is recorded as polymer A;
[0056] 2) At the same time as step 1), add ultrafine microcrystalline muscovite powder (particle size D 90 =2.5μm, loose density = 0.20g / cm 3 ) 50 parts, seaweed fiber powder (fiber strength: 1.8d, average particle size of 40μm) 10 parts, N,N-methylenebisacrylamide (chemically pure) 9 parts and distilled water 8800 parts, the mixture was initially stirred at room temperature for 40 minutes, then 1000 parts of acrylic acid (analytical pure) was added and the temperature was raised to 50°C, and the stirring was continued for 15 minutes. Two electrodes were inserted and gradient discharge was performed at 200V, 500V, and 800V for 3 minutes respectively, and then the temperature was raised to 60°C and the reaction was continued to be fully stirred for 15 minutes, and then cooled to room temperature, which was recorded as polymer B;
[0057] 3) Mixing polymer A and polymer B and stirring for 100 minutes, neutralizing with NaOH (30%) to a neutralization degree of 95%, then washing with distilled water for several times, and then washing with ethanol, sealing and placing in a 50° C. oven for 24 hours, removing the seal and placing in a dryer for drying for 5 hours, thereby obtaining the high-strength concrete internal curing agent.
[0058] According to the test, the tap water absorption rate of the internal nourishing agent obtained in this embodiment is 395g / g, and the water retention rate after soaking for 24 hours is 93.6%.
[0059] Application Example 2
[0060] The high-strength concrete internal curing agent obtained in Example 2 is applied to prepare high-strength concrete (C70 grade), and the specific steps include:
[0061] First, the internal curing agent obtained in Example 2 was fully stirred in water, and then coarse aggregate, fine aggregate and cementitious material (total design amount was 600 kg / m 3 ) was dry-mixed in a mixer for 40 seconds, and finally the internal curing mixture was poured into the mixer and fully mixed for 3 minutes. The slump of the concrete was controlled to be (200±20) mm by adjusting the amount of water reducing agent; see Table 3 for details, and the performance test results of the obtained concrete are shown in Table 4.
[0062] Table 3 Concrete mix ratio (kg / m 3 )
[0063] Group cement Fly ash Mineral powder sand stone water Water reducing agent Internal curing agent Benchmarks 500 50 50 922 775 145 14.7 Application Example 2 500 50 50 922 775 145 14.7 11.3
[0064] Table 4 Performance test results of high-strength concrete obtained in Application Example 2
[0065] Group Shrinkage expansion ratio (%) Compressive strength(MPa) Electric flux (C) Carbonization depth (mm) Age 28d 28d 56d 56d Benchmarks -0.058 86.8 670 3.02 Application Example 2 -0.046 95.5 480 2.17
[0066] The above results show that the high-strength concrete obtained in this application example can simultaneously improve the volume stability, mechanical properties and durability compared with the benchmark group without internal curing agent, as follows: in terms of volume stability, the shrinkage rate of concrete at the age of 28 days is reduced by 20%, in terms of mechanical properties, the compressive strength of concrete at the age of 28 days under standard curing is increased by 10%, and in terms of durability, the 56d electric flux of concrete under standard curing is reduced by 190C and the carbonization depth is reduced by 28%.
[0067] Comparative Example 1
[0068] A high-strength concrete internal curing agent, the preparation method of which comprises the following steps:
[0069] 1) Add 5000 parts of water to a beaker, weigh 0.5 parts of a composite nonionic surfactant according to the composite ratio of fatty alcohol polyoxyethylene ether and isomeric tridecanol polyoxyethylene ether of 1:1, add it to the water, place it in a 50°C water bath and stir to dissolve; then add 20 parts of sodium silicate solution (mass concentration of 35%) and 80 parts of methyldimethoxysilane, stir well for 40 minutes, then slowly add 0.5 parts of ammonia water (mass concentration of 25%), stir quickly (stirring rate of 300r / min) for 10 to 15 minutes while adding, and then seal;
[0070] 2) placing in a 50° C. oven for 24 hours, removing the seal and placing in a dryer for drying for 5 hours to obtain the internal curing agent.
[0071] After testing, the tap water absorption rate of the obtained internal curing agent was 220g / g, and the water retention rate was 79.5% after immersion for 24 hours; its water retention and water release properties were significantly reduced.
[0072] Comparative Example 2
[0073] A high-strength concrete internal curing agent, the preparation method of which comprises the following steps:
[0074] 1) Add ultrafine microcrystalline muscovite powder (particle size D 90 =2.5μm, loose density = 0.20g / cm 3) 60 parts, N,N-methylenebisacrylamide (chemically pure) 9 parts and distilled water 8800 parts, the mixture was initially stirred at room temperature for 40 minutes, then 1000 parts of acrylic acid (analytical pure) was added and the temperature was raised to 50°C, and the stirring was continued for 15 minutes, and two electrodes were inserted to discharge at 200V, 500V and 800V for 3 minutes, and then the temperature was raised to 80°C and the reaction was continued to be fully stirred for 15 minutes, and then cooled to room temperature;
[0075] 2) neutralize with NaOH (30%) to a neutralization degree of 95%, then wash with distilled water for several times, then wash with ethanol, seal and place in a 50° C. oven for 24 hours, remove the seal and place in a dryer to dry for 5 hours, to obtain the high-strength concrete internal curing agent.
[0076] After testing, the tap water absorption rate of the obtained internal nourishing agent is 200g / g, and the water retention rate is 76.4% after soaking for 24 hours.
[0077] The obtained concrete curing agent is applied to prepare high-strength concrete (C60 grade), and the specific steps include:
[0078] First, stir the internal curing agent in water, then add coarse and fine aggregates and cementitious materials (total design dosage is 560kg / m 3 ) is dry-mixed in a mixer for 40 seconds, and finally the internal curing mixture is poured into the mixer and fully mixed for 3 minutes. The slump of the concrete is controlled at (200±20) mm by adjusting the amount of water reducing agent. The specific mix ratio is shown in Table 5 below; the performance test results of the obtained concrete are shown in Table 6.
[0079] Table 5 Concrete mix ratio (kg / m 3 )
[0080] Group cement Fly ash Mineral powder sand stone water Water reducing agent Internal curing agent Benchmarks 400 50 110 605 1070 144 13.2 Comparative Example 2 400 50 110 605 1070 144 13.2 11.0
[0081] Table 6 Performance test results of high-strength concrete obtained in Comparative Example 2
[0082] Group Shrinkage expansion ratio (%) Compressive strength(MPa) Electric flux (C) Carbonization depth (mm) Age 28d 28d 56d 56d Benchmarks -0.056 74.1 735 3.35 Comparative Example 2 -0.050 70.4 675 3.42
[0083] After the concrete specimens were formed and hardened, the test showed that compared with the benchmark group without internal curing agent, the concrete shrinkage rate of Example 2 at the age of 28 days was reduced by 10% in terms of volume stability, and the compressive strength of the concrete at the age of 28 days under standard curing was reduced by 5%. In terms of durability, the electric flux of the concrete under standard curing was reduced by 60C at 56 days, and the carbonation depth was increased by 2%.
[0084] Comparative Example 3
[0085] A high-strength concrete internal curing agent, the preparation method of which comprises the following steps:
[0086] 1) Add 5000 parts of water to a beaker, take 0.5 parts of a composite nonionic surfactant of fatty alcohol polyoxyethylene ether and isomeric tridecanol polyoxyethylene ether in a composite ratio of 1:3, add it to water, place it in a 50°C water bath and stir to dissolve; then add 20 parts of sodium silicate solution (mass concentration of 35%) and 80 parts of methyldimethoxysilane, stir well for 40 minutes, then slowly add 0.5 parts of ammonia water (mass concentration of 25%), stir rapidly (stirring rate of 300r / min) for 10 to 15 minutes while adding, and then seal and mark as polymer A;
[0087] 2) At the same time as step 1), add ultrafine microcrystalline muscovite powder (particle size D 90 =10μm, loose density = 0.40g / cm 3 ) 45 parts, seaweed fiber powder (fiber strength: 1.8d, average particle size of 60μm) 15 parts, N,N-methylenebisacrylamide (chemically pure) 9 parts and water 8500 parts, the mixture was initially stirred at room temperature for 40 minutes, then 1000 parts of acrylic acid (analytical pure) was added and the temperature was raised to 50°C, and the stirring was continued for 15 minutes. Two electrodes were inserted and discharged at 500V for 8 minutes, and then the temperature was raised to 60°C and the reaction was continued for 15 minutes. Then, it was cooled to room temperature and marked as polymer B;
[0088] 3) Mixing polymer A and polymer B and stirring for 100 minutes, neutralizing with NaOH (30%) to a neutralization degree of 90%, then washing with distilled water for several times, and then washing with ethanol, sealing and placing in a 50° C. oven for 24 hours, removing the seal and placing in a dryer for drying for 5 hours, thereby obtaining the high-strength concrete internal curing agent.
[0089] After testing, the tap water absorption rate of the internal curing agent obtained in this comparative example is 280g / g, and the water retention rate after immersion for 24 hours is 83.3%; the water retention and water release performances of the obtained internal curing agent are significantly reduced.
[0090] Comparative Example 4
[0091] A high-strength concrete internal curing agent, the preparation method of which comprises the following steps:
[0092] 1) Add 5000 parts of distilled water into a beaker, take 0.5 parts of hexadecyltrimethylammonium bromide as a cationic surfactant and add it into the water, place it in a 50°C water bath and stir to dissolve; then add 20 parts of sodium silicate solution (mass concentration is 35%) and 80 parts of methyldimethoxysilane, stir well for 40 minutes, then slowly add 0.5 parts of ammonia water (mass concentration is 25%), stir rapidly (stirring rate is 300r / min) for 10 to 15 minutes while adding, and then seal, which is recorded as polymer A;
[0093] 2) At the same time as step 1), add ultrafine microcrystalline muscovite powder (particle size D 90 =3μm, loose density = 0.20g / cm 3 ), 45 parts of seaweed fiber powder (fiber strength: 1.8d, average particle size of 30μm), 15 parts of N,N-methylenebisacrylamide (chemically pure) 9 parts and 8500 parts of distilled water, the mixture was initially stirred at room temperature for 40min, then 1000 parts of acrylic acid (analytical pure) were added, the temperature was raised to 65°C, 0.5 parts of initiator potassium persulfate (analytical pure) was added and continued to be stirred evenly for 30min, a polymerization reaction occurred (the reaction process and the rate of reactant addition were strictly controlled), and then cooled to room temperature, marked as polymer B;
[0094] 3) The obtained polymer A and polymer B are mixed and stirred for 100 minutes, neutralized with NaOH (30%) to a neutralization degree of 90%, then washed with distilled water for several times, and then washed with ethanol, sealed and placed in a 50° C. oven for 24 hours, and after removing the seal, placed in a dryer and dried for 5 hours to obtain the high-strength concrete internal curing agent.
[0095] After testing, the high-strength concrete internal curing agent obtained in this comparative example has a tap water absorption rate of 265g / g, and a water retention rate of 81.2% after immersion for 24 hours; in addition, in step 2), the initiator is used to replace the discharge electrolysis reaction, which has the problems of difficult control of the reaction process and prone to violent polymerization due to uneven mixing.
[0096] The concrete curing agent obtained in this comparative example is applied to prepare high-strength concrete (C60 grade), and the specific steps are as follows:
[0097] First, stir the internal curing agent in water, then add coarse and fine aggregates and cementitious materials (total design dosage is 560kg / m 3 ) is dry-mixed in a mixer for 40 seconds, and finally the internal curing mixture is poured into the mixer and fully mixed for 3 minutes. The slump of the concrete is controlled at (200±20) mm by adjusting the amount of water reducing agent. The specific mix ratio is shown in Table 7 below; the performance test results of the obtained concrete are shown in Table 8.
[0098] Table 7 Concrete mix ratio (kg / m 3 )
[0099] Group cement Fly ash Mineral powder sand stone water Water reducing agent Internal curing agent Benchmarks 400 50 110 605 1070 144 13.2 Comparative Example 4 400 50 110 605 1070 144 13.2 11.0
[0100] Table 8 Performance test results of high-strength concrete obtained in Comparative Example 4
[0101] Group Shrinkage expansion ratio (%) Compressive strength(MPa) Electric flux (C) Carbonization depth (mm) Age 28d 28d 56d 56d Benchmarks -0.056 73.8 740 3.26 Comparative Example 4 -0.049 73.6 655 3.25
[0102] After the concrete specimens were formed and hardened, the test showed that compared with the benchmark group without internal curing agent, the concrete shrinkage rate of Example 4 at the age of 28 days was reduced by 12% in terms of volume stability. In terms of mechanical properties, the compressive strength of concrete at the age of 28 days under standard curing was basically the same. In terms of durability, the electric flux of concrete under standard curing was reduced by 85C at 56 days, and the carbonization depth was the same as the benchmark.
[0103] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A method for preparing a high-strength concrete internal curing agent, characterized in that: The steps include: 1) dissolving a composite nonionic surfactant in water, adding a sodium silicate solution and methyldimethoxysilane thereto, and stirring; then adding ammonia water under stirring conditions, and mixing evenly to obtain a polymer A; wherein the composite nonionic surfactant is composed of fatty alcohol polyoxyethylene ether and isomeric tridecanol polyoxyethylene ether; The raw materials used and their weight proportions include: 0.5-1 part of composite nonionic surfactant, 20-25 parts of sodium silicate solution, 75-80 parts of methyl dimethoxy silane, and 0.5-1 part of ammonia water; 2) Mixing the microcrystalline muscovite ultrafine powder, seaweed fiber powder, N,N-methylenebisacrylamide and water uniformly, preliminarily stirring the obtained mixture at room temperature, then adding acrylic acid and heating and stirring uniformly, performing glow discharge electrolytic plasma treatment, then heating and stirring reaction, and cooling to room temperature to obtain polymer B; The raw materials used and their weight proportions include: 45-50 parts of microcrystalline muscovite ultrafine powder, 10-15 parts of seaweed fiber powder, 8-10 parts of N,N-methylenebisacrylamide, 8250-9000 parts of water, and 900-1100 parts of acrylic acid; 3) Mixing and stirring polymer A and polymer B, neutralizing them to a neutralization degree of more than 90%, and then washing and drying them to obtain the internal curing agent.
2. The preparation method according to claim 1, characterized in that: The microcrystalline muscovite ultrafine powder has a particle size of D 90 ≤3μm, loose density ≤0.20g / cm 3 ; The sand content is ≤0.2%, the SiO2 content is 45~48%, and the Al2O3 content is 25~30%; the average particle size of the seaweed fiber powder is 30~40μm.
3. The preparation method according to claim 1, characterized in that: The mass ratio of fatty alcohol polyoxyethylene ether to isomeric tridecanol polyoxyethylene ether in the composite nonionic surfactant is 1:(1-1.5).
4. The preparation method according to claim 1, characterized in that: The mass concentration of the sodium silicate solution is 30-40%; the mass concentration of the ammonia water is 25-28%.
5. The preparation method according to claim 1, characterized in that: The glow discharge electrolytic plasma treatment step comprises: discharging and reacting for 2-3 min at voltage conditions of 180-220 V, 480-520 V, and 780-820 V, respectively.
6. The preparation method according to claim 1, characterized in that: Step 3) The mixing and stirring time is 100-120 min.
7. A high-strength concrete internal curing agent prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the high-strength concrete internal curing agent according to claim 7 in high-strength concrete, characterized in that: The content of the high-strength concrete internal curing agent in the high-strength concrete is 1.8-2.2% of the mass of the cementitious material.
Citation Information
Patent Citations
Preparation method of concrete maintenance agent with nano material
CN107010995A
Slow-release concrete curing agent, preparation method and application thereof
CN112299745A